PARTIAL BIOCHEMICAL CHARACTERIZATION OF EGG MASSES OF THE WEDGE SEAHARE DOLABELLA AURICULARIA (LIGHTFOOT, 1786) - Delan, Gloria G.; Pepito, Ador R.; Asakawa, Manabu; Yasui, K; Cuñado, Venerando D.; Maningo, Aurelia G.; Lamayo, Maria Helian A.; Rica, Rachel Luz V.; Abdon, Hector C.; Bontia, Presentation V.; Lamayo, Roberto C. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 16 No. 1, 2013, 2018)
Egg masses of the wedge seahare Dolabella auricularia are gathered as human food in the Visayas region and other areas in the Philippines, but there have been no studies examining their appropriateness for human consumption. This study was conducted to characterize the biochemical components of the egg masses. Biochemical characterization was assessed through proximate  composition  analysis and  an amino acid  profile. The egg masses comprised  91.10 percent moisture, 3.43 percent ash, 2.85 percent crude protein, 1.77 percent carbohydrates, and 0.85 percent fats. The 23 amino acid included six (6) essential components, nine (9) non -essential components, and eight (8) others. The essential amino acids included leucine, valine, isoleucine, phenylalanine, threonine and histidine, while the non-essential amino acids included  taurine, tyrosine, serine, glycine, aspartic acid, glutamic acid, alanine, glutamine and proline. The other components included phospho-serine, urea, aromatic amino acid, citrulline, beta-alanine, gamma- aminobutyric acid, ammonia and ornithine. The results show that egg masses contain amino acids that are important for human health, thus making it another food commodity from the ocean.